Solar power harvesting with metal modified windshield glass to obtain hot water - Mangas, Esteban (2022)
Energy solar harvesting through low environmental impact resources is an underlying objective for future technological developments. In this work, an innovative design of a vitro-metallic composite material is developed with Cu0, Zn0 and ZnO microparticles dispersed in a glass-ceramic matrix. The uppermost feature of these materials is that they are made of the reused of vehicle windshield glass disposed. The vitreous composite performance is evaluated in different seasons and under diverse weather conditions. The energy absorption is analyzed from the results of the UV-vis spectra and SEM images of the different composites. In this work it is demonstrated that the studied material has a good performance even in low temperature regions, reaching an efficiency between 30 to 50 [KJ/ KgH2O] with a 0.3% wt of metal-modified glass-ceramic material in water. The material response was analyzed through the composite material UV-vis spectrum. The new glass-ceramic materials are efficient in the process of heating water without the need of expensive devices or other forms of energy applications.